URGENSI REVITALISASI DAYCARE DALAM LINGKUNGAN KERJA RAMAH ANAK - Lulu El Maknun (Jurnal Harkat : Media Komunikasi Gender, 2018)
Abstract. UIN Syarif Hidayatullah Jakarta Daycare was established not only as a day care center, but also as a laboratory for the development of childcare at the beloved UIN campus. But in practice, Daycare seems to only run the work program of the Gender and Children's Study Center. Many things have been a factor in the narrowing of the opinion of the academic community on the connotation that UIN Syarif Hidayatullah Jakarta Daycare is only a formality and has not been able to accommodate the needs of its employees. To assess the urgency of Daycare revitalization, SWOT analysis is carried out which is commonly done at each institution. After getting the results of the analysis, the author recommends important points that are expected to revitalize Daycare, including improving quality, improving the system, adding infrastructure and evaluating. In conclusion, UIN Jakarta Daycare is very likely to become a childcare laboratory, but it requires the application of noble values such as courage and openness in carrying out management functions (POAC) for the creation of a child-friendly work environment at UIN Syarif Hidayatullah Jakarta.Abstrak. Daycare UIN Syarif Hidayatullah Jakarta didirikan bukan hanya sebagai tempat penitipan anak semata, tetapi merupakan laboratorium pengembangan pengasuhan anak di kampus UIN tercinta. Namun pada prakteknya, Daycare seolah hanya menjalankan program kerja Pusat Studi Gander dan  Anak. Ada banyak hal yang menjadi faktor mengerucutnya opini civitas akademika pada konotasi bahwa Daycare UIN Syarif Hidayatullah Jakarta hanya formalitas dan belum mampu mengakomodir kebutuhan pegawainya. Untuk mengkaji sejauh mana urgensi revitalisasi Daycare dilakukan analisis SWOT yang lazim dilakukan pada setiap lembaga. Setelah  mendapatkan hasil analisis, penulis merekomendasikan poin-poin penting yang diharapkan dapat merevitalisasi Daycare, di antaranya peningkatan mutu, perbaikan sytem, penambahan infrastruktur dan evaluasi. Kesimpulannya Daycare UIN  Jakarta sangat mungkin untuk menjadi laboratorium pengasuhan anak, namun  dibutuhkan aplikasi nilai-nilai luhur seperti keberanian dan keterbukaan dalam menjalankan fungsi managemen (POAC) demi terciptanya atmosfir  lingkungan kerja ramah anak di UIN Syarif Hidayatullah Jakarta.